CXCL12 estimula fibroblastos pulmonares a produzir CCL3, CXCL2, LTB4 e LTC4 via p38, MEK1/2, PI-3K e JNK - Danilucci, Taís Marolato [UNESP] (2013)
C-X-X motif ligand 12 (CXCL12) and its specific receptor Chemokine receptor 4 (CXCR4) play a critical role in airway inflammation. However, the effects of CXCL12/CXCR4 axis on pulmonary fibroblast activation are unknown. In this study, we investigated the effect of CXCL12/CXCR4 axis on chemokine (C-C motif) ligand 3 (CCL3), chemokine (C-X-C motif) ligand 2 (CXCL2), leukotrienes B4 (LTB4) and C4 (LTC4) production by pulmonary fibroblasts and the intracellular signaling involved in the process. CXCL12 induced CCL3, CXCL2, LTB4 and LTC4 production, and CCL3 production is not dependent on CXCL2; but CXCL2 production is dependent on CCL3 production. LTB4 production can be partially down-regulated by CXCL2 and CCL3 production and LTC4 production is dependent on CCL3 and CXCL2 production. Pulmonary fibroblasts constitutively expressed CXCR4, and CXCL12 stimulation up-regulated its expression. Western blot analysis showed that CXCL12 increased protein expression of CXCR4 and induced phosphorylation at S339 of CXCR4. Constitutive CXCR4 expression was decreased by anti-CCL3 antibody or MK 886. Inducible CXCR4 was inhibited by anti-CXCL2 antibody. Indeed pulmonary fibroblasts were pretreated with MK886, dexamethasone (Dexa) and loratadine (Lor). MK886 and loratadine was able to reduced LTB4 and LTC4 production but not CCL3 and CXCL2. Dexa decreased CCL3, CXCL2, LTB4 and LTC4 production, and when associated with Lor this decrease was more effective. We found that PI-3K and JNK intracellular signaling play a role in CCL3 production; p38, MEK1/2, PI-3K and JNK are involved in CXCL2 production and p38 and MEK1/2 pathways are involved in LTB4 production by...